Resolution of mathematical problems with fractions focused on the school context - Avella Tuta, Diana Paola; Salazar Pérez, Fabio Ahirton; Miguez García, José Edilberto (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article discloses the partial results of a qualitative approach research of an educational action type, which is aimed at developing a didactic proposal for the teaching of mathematics. The research focuses on the subject of the teaching of solving mathematical problems with fractions, with sixth grade children of the “Carlos Alberto Olano Valderrama” Educational Institution in Belén (Boyacá). The proposal consists of focusing the teaching from the resolution of problems. This proposal has been made in three moments: the first one, the review of background and theoretical discussion; the second, the application and analysis of the results of the diagnostic test; and the third, the design, application and evaluation of the didactic strategy. Obtaining that 60 % of the students appropriated the method satisfactorily, 30 % required more accompaniment and 10 % of the students did not appropriate the method.